The pharmacological properties and corresponding mechanisms of farrerol: a comprehensive review. (1st January 2022) - Qin, Xiaojiang; Xu, Xinrong; Hou, Xiaomin; Liang, Ruifeng; Chen, Liangjing; Hao, Yuxuan; Gao, Anqi; Du, Xufeng; Zhao, Liangyuan; Shi, Yiwei; Li, Qingshan
Abstract: Context: Farrerol, a typical natural flavanone isolated from the traditional Chinese herb 'Man-shan-hong' [ Rhododendron dauricum L. (Ericaceae)] with phlegm-reducing and cough-relieving properties, is widely used in China for treating bronchitis and asthma. Objective: To present the anti-inflammatory, antioxidant, vasoactive, antitumor, and antimicrobial effects of farrerol and its underlying molecular mechanisms. Methods: The literature was reviewed by searching PubMed, Medline, Web of Knowledge, Scopus, and Google Scholar databases between 2011 and May 2021. The following key words were used: 'farrerol, ' 'flavanone, ' 'anti-inflammatory, ' 'antioxidant, ' 'vasoactive, ' 'antitumor, ' 'antimicrobial, ' and 'molecular mechanisms'. Results: Farrerol showed anti-inflammatory effects mainly mediated via the inhibition of interleukin (IL)-6/8, IL-1β, tumour necrosis factor(TNF)-α, NF-κB, NO, COX-2, JNK1/2, AKT, PI3K, ERK1/2, p38, Keap-1, and TGF-1β. Farrerol exhibited antioxidant effects by decreasing JNK, MDA, ROS, NOX4, Bax/Bcl-2, caspase-3, p-p38 MAPK, and GSK-3β levels and enhancing Nrf2, GSH, SOD, GSH-Px, HO-1, NQO1, and p-ERK levels. The vasoactive effects of farrerol were also shown by the reduced α-SMA, NAD(P)H, p-ERK, p-Akt, mTOR, Jak2, Stat3, Bcl-2, and p38 levels, but increased OPN, occludin, ZO-1, eNOS, CaM, IP3R, and PLC levels. The antitumor effects of farrerol were evident from the reduced Bcl-2, Slug, Zeb-1, and vimentin levels but increased p27, ERK1/2, p38, caspase-9, Bax, and E-cadherin levels. Farrerol reduced α-toxin levels and increased NO production and NF-κB activity to impart antibacterial activity. Conclusions: This review article provides a theoretical basis for further studies on farrerol, with a view to develop and utilise farrerol for treating of vascular-related diseases in the future.